2019
DOI: 10.1177/1098612x19828131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music on behavior and physiological stress response of domestic cats in a veterinary clinic

Abstract: Objectives Our objective was to determine if feline-specific music played in a veterinary clinical setting would promote lower cat stress scores (CSSs), lower mean handling scale scores (HSs) and reduced neutrophil:lymphocyte ratios (NLRs) in cats during physical examinations. Methods Cats were exposed to one of three auditory stimuli tests – silence, classical music and cat-specific music – during three physical examinations 2 weeks apart. CSSs were recorded at pre- and post-auditory tests and during the exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 21 publications
2
22
0
2
Order By: Relevance
“…Efforts to date have succeeded in enforcing certain measures based on a deeper understanding of the biology and behaviour of cats-for instance, practical improvements such as sound insulation of housing units from dog sounds and other stressful sounds, access to windows and natural light sources, sufficient number of hiding places and elevated locations or placement of housing units above floor level, giving cats a greater sense of security [105,284,285]. The current research also focuses on procedures and methods of management and enrichment of the environment (e.g., playing specific music to cats to relieve stress [286], various forms of olfactory [287,288], cognitive [289,290], visual [291], food [292], pheromone enrichment [293] or social enrichment in the form of human interaction [103]). Another trend in the design of new facilities is group housing of cats, but opinions on it differ in the scientific community.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to date have succeeded in enforcing certain measures based on a deeper understanding of the biology and behaviour of cats-for instance, practical improvements such as sound insulation of housing units from dog sounds and other stressful sounds, access to windows and natural light sources, sufficient number of hiding places and elevated locations or placement of housing units above floor level, giving cats a greater sense of security [105,284,285]. The current research also focuses on procedures and methods of management and enrichment of the environment (e.g., playing specific music to cats to relieve stress [286], various forms of olfactory [287,288], cognitive [289,290], visual [291], food [292], pheromone enrichment [293] or social enrichment in the form of human interaction [103]). Another trend in the design of new facilities is group housing of cats, but opinions on it differ in the scientific community.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to implementation of low-stress handling procedures, 6 clinic-related stress mitigation measures have included pharmacological agent administration [25][26][27] and environmental changes. 6,28 However, choice of where to perform the physical examination is rarely considered. One practical application at this institution of the results of this study is that, whenever possible, procedures are restricted to examination rooms with the owner present, with more frequent use of feline-only examination rooms provided with catnip and hiding places.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, playing soothing background music (classical music or commercially available recordings) has been recommended [19]. One study indicated that music specifically designed for cats (but not classical music) was associated with fewer stress indicators and reduced resistance to handling during a clinical examination compared to no background music [50]. In dogs, some studies suggest a possible calming effect of music (reviewed in [51], but the only study performed in a veterinary context could not demonstrate a reduction in fearful or aggressive behaviour.…”
Section: Sensory Considerationsmentioning
confidence: 99%
“…In dogs, some studies suggest a possible calming effect of music (reviewed in [51], but the only study performed in a veterinary context could not demonstrate a reduction in fearful or aggressive behaviour. However, owners found the waiting time more pleasant and veterinarians indicated that they enjoyed the music [50]. Further studies are needed to adress species-specific preferences, as well as individual responses [51].…”
Section: Sensory Considerationsmentioning
confidence: 99%